SISTEM HIDROLIK UNTUK MENUNJANG PROSES PENGECORAN BERTEKANAN UNTUK KOMPONEN OTOMOTIF - , Buana Yaksa Surya Atmaja, Dr. Suyitno,S.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Metal casting process with pressure are produce casting has high density and precision product. In application hydraulic system is often as the driven machine HPDC which is called high pressure die casting. After assembly hydraulic system into machine, it was used for cast with metal molten. Casting products in this experiments with injection pressure variation from plunger to mould cavity i.e 50 kg/cm2, 75 kg/cm2 dan 100 kg/cm2. Plunger constant velocity is 6,67 cm/s. When its velocity is slower than 6,67 cm/s it will be fault casting products and then the biscuit of casting will become thicker and the molten metal become solid before filling mould cavity, in the end it will be difficult to take off casting product from machine. From experiment it is shown casting products happens to increase physic and mechanical properties or better than gravity casting, with process for 8 second. Optimum product at variation injection pressure at 50 kg/cm2 ,moulding heating temperature at 300oC, melting aluminum temperature 700oC and Injection pressure metal molten 75 kg/cm2 ,moulding heating temperatur 350oC, melting aluminum temperature 750oC. To apply this system the firs step time is define circuit system from hydraulic, the maximum pressure can be reached by hydraulic cylinder. The other stage explain the maintenance process and trouble shooting with repairing this driven system.